THE EFFECT OF ISLAMIC FINANCIAL LITERACY ON GENERATION Z’S INTEREST IN GOLD INVESTMENTS IN PAMEKASAN REGENCY - Fitriyatus Zinah; Risca Dwiaryanti (PT. Altin Riset Publishing, 2026)
This study aims to determine the effect of Islamic financial literacy on Generation Z’s interest in investing in gold in Pamekasan Regency. Generation Z, as a productive age group that is adaptable to technological developments, holds great potential in the investment world, including in gold an instrument considered safe and stable. However, in the context of Muslim society, an understanding of Islamic finance principles is a crucial factor in making investment decisions aligned with Islamic values. The research method employed is a quantitative approach, utilizing data collection procedures such as observation, interviews, documentation, and a questionnaire. The population for this study consists of Generation Z in Pamekasan Regency, with a sample size of 100 respondents selected using probability sampling. The results of the study indicate that Islamic financial literacy has a positive and significant influence on Generation Z’s interest in gold investment. The higher the level of Islamic financial literacy they possess, the greater their interest in choosing gold investment as one of their financial instruments.